1980
DOI: 10.1530/acta.0.0930264
|View full text |Cite
|
Sign up to set email alerts
|

Panhypopituitarism secondary to head trauma: evidence for a hypothalamic origin of the deficit

Abstract: A complete endocrinological exploration was performed in a 23 year old male patient who presented clinical signs of an acquired panhypopituitarism which appeared two months after a severe head trauma, in order to determine whether the deficit lay in the hypothalamus or in the pituitary. TSH had normal basal levels, but presented a delayed rise after TRH administration. PRL rose normally after TRH administration, but presented a blunted response to both metoclopramide and insulin tolerance test. Cortisol rose s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…There is a clear relationship between DAI and cognitive, neuropsychological and behavioural deficits such as impaired processing speed and alterations with impaired day-to-day function (Tate et al, 1991;Felmingham et al, 2004). Somatic deficits such as isolated decreases of pituitary hormones (Klingbeil and Cline, 1985) or even panhypopituitarism (Jambart et al, 1980) and other intracerebral biochemical pathway disorders have been reported (van Woerkom et al, 1977;Rossi, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…There is a clear relationship between DAI and cognitive, neuropsychological and behavioural deficits such as impaired processing speed and alterations with impaired day-to-day function (Tate et al, 1991;Felmingham et al, 2004). Somatic deficits such as isolated decreases of pituitary hormones (Klingbeil and Cline, 1985) or even panhypopituitarism (Jambart et al, 1980) and other intracerebral biochemical pathway disorders have been reported (van Woerkom et al, 1977;Rossi, 1998).…”
Section: Discussionmentioning
confidence: 99%